Functional Integration and Segregation in Multiplex Brain Networks for Alzheimer's Disease - Cai, Lihui; Wei, Xile; Liu, Jing; Zhu, Lin; Wang, Jiang; Deng, Bin; Yu, Haitao; Wang, Ruofan (Frontiers in Neuroscience, 2020)
Growing evidence links impairment of brain functions in Alzheimer’s disease (AD) with disruptions of brain functional connectivity. However, whether the AD brain show similar changes from a dynamic or cross-frequency view remains poorly explored. This paper provides an effective framework to investigate the properties of multiplex brain networks in AD considering inter-frequency and temporal dynamics. Two types of multiplex networks were reconstructed separately considering the network interactions between different frequency bands or time points. We further applied multiplex network features to characterize functional integration and segregation of the cross-frequency or time-varying networks. Finally, machine learning methods were employed to evaluate the performance of multiplex-network-based indexes for detection of AD. Results revealed that the brain networks of AD patients are disrupted with reduced segregation particularly in left occipital area for both cross-frequency and time-varying networks. However, the alteration of integration differs among brain regions and may show an increasing trend in the frontal area of AD brain. By combing the features of integration and segregation in time-varying networks, the best classification performance was achieved with an accuracy of 92.5%. These findings suggest that our multiplex framework can be applied to explore functional integration and segregation of brain networks and characterize the abnormalities of brain function. This may shed new light on the brain network analysis and extend our understanding of brain function in patients with neurological diseases.